HUBUNGAN PENGELOLAAN SAMPAH DENGAN KEJADIAN DIARE DI DESA PANDANAN - I PUTU BAYU AGUS SAPUTRA; I PUTU DEDY ARJITA; IRWAN SYUHADA; I GEDE ANGGA ADNYANA (Universitas Mahasaraswati K. Mataram, 2024)
Pandanan Hamlet is a favorite tourist destination in Lombok, admired by tourists for its beautiful beaches. Diarrhea represents a common and potentially serious global health issue, especially in areas with limited access to healthcare. This condition, characterized by increased frequency and fluidity of stool, can be caused by various factors ranging from bacterial or viral infections to chronic medical conditions. This research focuses on Pandanan Village, examining the impact of waste management on the incidence of diarrhea. Waste management is a crucial environmental issue worldwide. Improperly managed waste, encompassing various materials from household to industrial waste, can become a source of disease spread. The study indicates a correlation between good waste management and a decrease in diarrhea incidents. Results show a significant relationship (P<0.05) between poor waste management and increased diarrhea incidence, with poor waste management being linked to 22 cases of diarrhea. These findings underscore the importance of proper waste management as a preventive measure against diarrhea, particularly in the context of sanitation and environmental cleanliness. This research provides crucial insights into the relationship between environmental factors and public health, highlighting the need for interventions focused on improving sanitation infrastructure and health education in Pandanan Village.